Biocomposite material to enhance heat transfer of wood (Shorea Faguetiana and Palaquim SP) for green building in Malaysia - Siti Aminah Ibrahim; Mazlan Mohamed; Sitti Fatimah Mohd Ramle; Mohd Hazim Mohamad Amini; M.S. Abdul Aziz; Zairi Ismael Rizman (2015)
This paper presents a review of material efficiency that became one of major component of green building. Selections of materials from renewable and recycled sources are encouraged since it can help to minimize environmental impact, especially on waste production. The uses of materials that contain recycled content are the third priority for selecting building products. In the construction industry, bio-composite is a new material developed for building materials. It is believe that bio-composites or natural fibre composite can be an economical material for construction. In this study, the performance of bio-composite on wood to enhance heat transfer is investigated. The models of house are building using two types of Malaysian wood, Nyatoh (Shorea Faguetiana) and Meranti (Palaquim Sp.) with addition of bio-composites from saw dust and rice husk. The results of experiment are then compared with simulation result that has done using GAMBIT and FLUENT software.